Effect of plant extracts of Salvia officinalis L. and Costus speciosus L. in growth of some bacteria species isolated from urinary tract infections in Samarra city - Huda Ali Hadi; Rasheed H. Hasan (Tikrit Journal of Pure Science, 2020)
The present study aimed to investigate the inhibitory effect of alcoholic extract (methanol - ethanol) and flavonoids by diffusion  methods of wells of Salvia officinalis L. and Costus speciosus L. plants on Escherichia . coli and Proteus  spp. isolated from patients with urinary tract infection Samarra city, the samples were collected during the period from 15/7/2018 to 30/9/2018, It was found through the results that the extracts plant that used in this study showed various inhibitory effect against, The bacteria species study imitation , where on differ this effect by difference the concentration that used and type the plant extract , showing  E.coli significant difference at significant (p< 0.05) in inhibition diameter of alcoholic (methanol) extract for Salvia officinalis L. (10.61±7.5) at higher concentration used, while these bacteria showed on significant difference in the level of inhibition diameter of alcoholic (ethanolic) extract for Salvia officinalis L., whereas the flavonoids Netted significant difference of these plant in some of concentration that used comparied with the antibiotic that used in this study. Either regarding proteus spp. bacteria notted no significant difference of both the Costus speciosus L. and Salvia officinalis L. by using the alcoholic (ethanolic) extract, while the flavonoids extract showed no significant difference in Costus speciosus L., whereas showed high significant difference in flavonoids extract of Salvia officinalis  L., due to the fact that the flavonoids extract is one of the active substance that done laboratory extraction for both the plants where that higher inhibitory effect of microbial growth from the alcoholic (ethanolic – methanolic) extract of plants .